PENGARUH LEVERAGE, PROFITABILITAS, SALES GROWTH, DAN FIRM SIZE TERHADAP FINANCIAL DISTRESS - Jennifer Patricia; Rosmita Rasyid (Jurnal Paradigma Akuntansi, 2026)
This research aims to find empirical evidence related to the effect of Leverage, Profitability, Sales Growth, Firm Size on a company's financial distress. The population is the basic materials companies listed on the Indonesian Stock Exchange from 2019-2021. The method used is purposive sampling, a sample of 23 companies was obtained . The data analysis used in this research is Multiple Linear Regression Analysis. The analysis program used is Eviews 12. The results show that profitability has a negative effect on financial distress, and firm size has a positive effect on financial distress. While leverage and sales growth have no effect on financial distress. The implication of this research is that companies need to improve efficiency so that there is an increase in profits so as to prevent financial distress.